Comparison of Fungal Genera Isolated from Cucumber Plants and Rhizosphere Soil by Using Various Cultural Media - Chong-Yang Cheng; Ming-Yuan Zhang; Yong-Chun Niu; Meng Zhang; Yue-Hua Geng; Hui Deng (Journal of Fungi, 2023)
Plant endophytic fungi and rhizosphere soil fungi are often reported as biocontrol agents against plant pathogens or with plant growth promotion potential. Four treatments were performed in field and greenhouse experiments where cucumber plants were inoculated with Trichoderma harzianum and Fusarium oxysporum in 2022. The roots, stems and leaves of cucumber plants and their rhizosphere soil were collected twice individually from the field and greenhouse for isolation of cucumber endophytic and rhizosphere soil fungi. All fungal strains were identified through sequence similarity of the ITS1-5.8s-ITS2 rDNA region. The potato dextrose agar (PDA) media yielded the highest number of genera isolated from cucumber plants, rhizosphere soil and both compared to other media. There were no significant differences among the four media for the isolation of all cucumber endophytic fungi. However, in the roots, the number of endophytic fungi isolated by MRBA was significantly higher than that isolated on malt extract agar (MEA), while in the stems, the number of fungi isolated with PDA was significantly higher than that isolated with Martin’s rose bengal agar medium (MRBA). PDA had significantly higher isolation efficiency for the rhizosphere soil fungi than MRBA. The 28 fungal genera had high isolation efficiency, and the endophytic Trichoderma strains were significantly more isolated by MEA than those of MRBA. It is suggested that PDA can be used as a basic medium, and different cultural media can be considered for specific fungal genera.